Answer:
z-4
Step-by-step explanation:
z(5z²-80) ÷ 5z(z+4) = z-4
Step-by-step explanation:
Given: z(5z²-80) ÷ 5z(z+4)
Calculation:
First we factor numerator z(5z²-80)
Take out 5 from 5z²-80 and we get 5z(z²-16)
Now we factor 16 = 4²
5z(z²-4²)
Using formula, (a²- b²)=(a+b)(a-b)
5z(z²- 4²)⇒5z(z+4)(z-4)
Simplified fraction
5z(z+4)(z-4) ÷ 5z(z+4)
Cancel like factor from numerator and denominator
⇒ z-4
Thus, z(5z²-80) ÷ 5z(z+4) = z-4
Answer:
approx. 15.23
Step-by-step explanation:
6^2+14^2=c^2
The answer for you're question is 4600
Are you add or subtracting
SUBTRACTION
3 1/4- 1 1/4 = 1 3/4
Addition
3 1/4-1 1/4= 4 3/4
Answer:
3125
Step-by-step explanation:
Cuz it is. I 4=5